Enantioselective Phosphine‐Catalyzed Formal [4+4] Annulation of α, β‐Unsaturated Imines and Allene Ketones: Construction of Eight‐Membered Rings. (10th October 2017) - Ni, Huanzhen; Tang, Xiaodong; Zheng, Wenrui; Yao, Weijun; Ullah, Nisar; Lu, Yixin
Abstract: The first highly enantioselective phosphine‐catalyzed formal [4+4] annulation has been developed. In the presence of amino‐acid‐derived phosphines, the unprecedented [4+4] annulations between benzofuran/indole‐derived α, β‐unsaturated imines and allene ketones proceeded smoothly, thus affording azocines, bearing either a benzofuran or an indole moiety, in excellent yields and with nearly perfect enantioselectivities (≥98 % ee in most cases). This work marks the first efficient asymmetric construction of optically enriched eight‐membered rings by phosphine catalysis.